Raw Milk: Fact or Fiction - Michelle A. Zitt; Ron Schmidt; Karla P. Shelnutt (EDIS, 2012)
The use of raw milk as a beverage for humans is a hotly debated topic. A simple Internet search using the term “raw milk” yields conflicting claims about its benefits and dangers. Many people base their opinions about raw milk on myths rather than facts. Not knowing the risks may lead people to drink raw milk and risk illness from harmful bacteria. If you are thinking about adding raw milk to your diet, or if you are curious about the debate, then this 5-page fact sheet will help you sort through the myths and facts of the raw milk debate. Written by Michelle A. Zitt, Ron Schmidt, and Karla P. Shelnutt, and published by the UF Department of Family, Youth and Community Sciences, March 2012.